The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1159/000520960
|View full text |Cite
|
Sign up to set email alerts
|

Potential Application of Low-Intensity Pulsed Ultrasound in Delaying Aging for Mice

Abstract: <b><i>Introduction:</i></b> The low-intensity pulsed ultrasound (LIPUS) is one of the popular treatment modalities allowing to boost the proliferation, differentiation, and migratory activity of cells, which might be a powerful strategy for anti-aging. Seeking a novel setup for LIPUS would benefit the development of ultrasound therapeutics. <b><i>Methods:</i></b> Here, we proposed a novel underwater exposure setup of LIPUS. C57BL/6 mice were reared in the designa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
(50 reference statements)
1
2
0
Order By: Relevance
“…3). Together with recent literature demonstrating that LIPUS can reduce senescent marker (P16 INK4a ) in aged mouse 131 , LIPUS treatment appears to have potential anti-aging effects on microglia.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…3). Together with recent literature demonstrating that LIPUS can reduce senescent marker (P16 INK4a ) in aged mouse 131 , LIPUS treatment appears to have potential anti-aging effects on microglia.…”
Section: Discussionsupporting
confidence: 60%
“…LIPUS not only has the potential to improve tissue-microelectrode bio-integration for BCIs, but also provide a new opportunity for treating other dysfunctions in biological processes 131,132 , CNS injuries 133 and neurodegenerative diseases [134][135][136] . For example, in response to ischemic injury, microglia migrate toward the injury site to phagocytose cell debris and protect damaged cells, reducing the inflammation caused by dead cell corpses 137 .…”
Section: Discussionmentioning
confidence: 99%
“…IL-7 is intrinsically involved in T cell homeostasis as an essential cytokine that enhances the persistence of T cells in vivo [ 21 ]. Our previous study [ 22 ] found that IL-2 and IL-7 levels in the spleen were still elevated in middle-aged (12–14 months old) C57BL/6 mice after LIPUS underwater irradiation and after one month of follow-up. The present study additionally demonstrates the significant impact of LIPUS on the release of upgraded IL-2 and IL-7.…”
Section: Discussionmentioning
confidence: 99%